PEMASANGAN PEMANAS AIR BAK PEMBENIHAN IKAN BERBASIS ARDUINO DAN PLTS UNTUK MENINGKATKAN KETAHANAN PANGAN - I W Jondra; I M Aryasa Wiryawan; I G Suputra Widarma; IGP Mastawan; I G N A Dwijaya Saputra (Dharma: Jurnal Pengabdian Masyarakat, 2020)
The Covid-19 pandemic was accompanied by food security threat, due by economic disruptions. The pandemic and the winter is increasingly food security threat in Desa Lumbung, Selemadeg Barat, Tabanan, Bali. In Bali, winter usually occurs between July and November, it has an impact on the lower water temperature, which triggers the harvest failure of the fish seed, because the water temperature lower than 25 degrees celcius, but fish seed well grow up in the range of water temperature 25 to 30 degrees celcius.The Department of Electrical Engineering of the State Polytechnic of Bali has carried out community service activities in Desa Lumbung. The activities is training to construction, operation and maintenance of arduino-based of water heaters for fish seed pond and solar power plants, which have been proven to be able to maintain water temperature. Even though in the winter the water temperature is maintained between 25 to 30 degrees celcius, it maintains the harvest of fish seeds   every 45 days. The success of this harvest will support food security in Desa Lumbung.Solar power plants are chosen as an energy source, because that is a green energy. This is in line with the Bali State Polytechnic as a center of excellent  technology for green tourism. The output of this activities is proven, it must  to be massive done and the government must increases the budget for the implementation. Food security is very important to maintain the stability of the Republic of Indonesia.